2014
DOI: 10.1021/jp4101619
|View full text |Cite
|
Sign up to set email alerts
|

Improved Oxygen Reduction Performance of Pt–Ni Nanoparticles by Adhesion on Nitrogen-Doped Graphene

Abstract: Graphene and its derivatives hold great potential as support for nanocatalyst in various energy applications, such as fuel cells, batteries, and capacitors. In this work, we used density functional theory to analyze substrate effect on the electrocatalytic activity of Pt–Ni bimetallic nanoparticles for oxygen reduction reaction (ORR). The dissociative mechanism is used to evaluate the ORR performance (energy barrier for O2 dissociation, free energy of intermediates, d-band center, overpotential, and electroche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 44 publications
4
54
0
Order By: Relevance
“…We propose that the intimate mixing is effectuated by that the dispersed N-dopant sites on the nanotubes function as effective anchoring points for the nanorods. [ 45,46 ] Moreover, at several locations it is observed that the N-CNTs penetrate through the nanorods (see also Figure S1, Supporting Information). Coupled with the fi rm attachment of the N-CNTs onto the CP substrate, it is clear that facile and stable charge-transport paths between the nanorods and the current collector are available.…”
Section: The Electrocatalyst Electrodementioning
confidence: 96%
“…We propose that the intimate mixing is effectuated by that the dispersed N-dopant sites on the nanotubes function as effective anchoring points for the nanorods. [ 45,46 ] Moreover, at several locations it is observed that the N-CNTs penetrate through the nanorods (see also Figure S1, Supporting Information). Coupled with the fi rm attachment of the N-CNTs onto the CP substrate, it is clear that facile and stable charge-transport paths between the nanorods and the current collector are available.…”
Section: The Electrocatalyst Electrodementioning
confidence: 96%
“…The binding energy and relative stability of the supported clusters depend not just upon the composition but also upon how the cluster is adsorbed onto graphene, whether in the face-on configuration or the edgeon configuration. A PtNi cluster was also placed on non-defective graphene and nitrogen-doped graphene surfaces [569]. The PtNi cluster was obtained by replacing the two inner Pt layers from the octahedral Pt 44 nanoparticle by Ni atoms, resulting in a 1:1.2 Pt:Ni cluster.…”
Section: Platinum Clustersmentioning
confidence: 99%
“…Adapted from Ref. [569]. the electronic band structures of Pt/CNT systems are very sensitive to the small changes in the geometries of Pt clusters and chains [577].…”
Section: Platinum Clustersmentioning
confidence: 99%
“…Of particular interest from the point of view of reducing the amount of Pt in ORR catalyst materials are intermetallic core-shell nanocatalysts (IMCs) 216 , see Fig 12. In addition to the significant complexities in synthesising these materials, as well as organising their stable arrangement on a graphene surface, there will also be challenges in modeling these catalysts -see Gracia-Espino et al 243 for an example. Advances in synthetic strategies for shape-controlled catalytic metal NPs may also motivate more detailed quantum chemical studies of supported metal clusters in terms of predicting facet-specific reactivities for the ORR.…”
Section: Fuel Cellsmentioning
confidence: 99%